INTRODUKSI PROSES PEMBUATAN PAKAN AYAM SKALA INDUSTRI MENENGAH di BLANG BINTANG ACEH BESAR - Edy Fradinata; Aman Yaman; Dasrul, Dasrul (JURNAL PENGABDIAN MANDIRI, 2022)
Chicken eggs as a source of nutrition for the people of Aceh in particular, have become a big problem at this time because they always have a dependence on the province of Medan. This dependence makes it difficult for Aceh to control egg prices at the market level. Market opportunities for egg needs are still wide in the province of Aceh (Egg needs 1-2 million eggs/day). With a large market share, it is appropriate if Aceh has a feed factory that can meet the needs of poultry feed. A medium-scale feed mill with a capacity of 8-15 tons/day has been built by the Aceh Government with factory operations carried out by the Aceh Animal Husbandry Service UPTD. This medium-scale factory produces to meet the need for an open house in Blang Bintang, Aceh Besar. To ensure a sustainable product, the factory must also ensure the continuous availability of quality raw materials. But in reality, the factory has a little difficulty in meeting the needs of corn, which is the main raw material for animal feed. Another thing that becomes a problem is, unstable prices, unstable amount of concentrate material, government policies, transportation and others are the main obstacles in this feed industry. Thus, the management of the availability of raw materials must be strengthened to ensure its smooth operation